A Versatile Approach for the Synthesis of Thiobarbiturate Analogues. (1st April 2015) - Zhou, Xiaokun; Chen, Ling‐Yan; Sun, Zhihua
Abstract : Abstract : A variety of 5‐substituted thiobarbiturates can be efficiently prepared in moderate to good yields. This protocol is broadly applicable and versatile, starting from substituted malonates and thiourea.